Deposição de nutrientes na carcaça de girinos de rã-touro - Mansano, Cleber Fernando Menegasso [UNESP] (2013)
The objective of this work was to determine nutrient deposition on the carcass of bullfrog (Lithobates catesbeianus) tadpoles using a nonlinear model. A total of 2,700 tadpoles with an average weight of 0.039 g were used. Commercial ground feed containing 55% crude protein was offered ad libitum. The animals were weighed and evaluated every ten days for analysis of crude protein, ether extract, water, and mineral salt contents. The parameters of the Gompertz model were estimated by the modified Gauss-Newton method, and the deposition rates (g per day) over time were calculated by the resulting equation. The values found for the parameters of the Gompertz equation, used to describe nutrient deposition on tadpole carcass, showed biological interpretation. Maximum deposition rate (t*) was observed on the 36.2331th day for protein, on the 37.1420th day for water, on the 35.2971th day for mineral salt, and on the 41.3547th day for fat. Nutrient intake from the diet is higher than the deposition rate on the tadpole carcass.